2004
DOI: 10.1007/s00134-004-2299-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of pro-brain natriuretic peptide in patients with cardiovascular complications following off-pump coronary artery surgery

Abstract: NT-pro-BNP levels measured before and immediately after off-pump coronary artery bypass seem to be predictive of postoperative cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
6
24
1
Order By: Relevance
“…3 Gill et al studied the kinetic release of NT-proBNP during acute myocardial infarction, and thus showed that this molecule peaked at 24 h after the acute event to a much greater extent than did BNP. 23 In the context of CABG, our data agree with the study of Kerbaul et al, 24 who reported a maximal release of NTproBNP 48 h after off-pump surgery, because the BNP values reached maximal values after 4 days, as suggested by our results (see Fig. 2).…”
Section: Discussionsupporting
confidence: 94%
“…3 Gill et al studied the kinetic release of NT-proBNP during acute myocardial infarction, and thus showed that this molecule peaked at 24 h after the acute event to a much greater extent than did BNP. 23 In the context of CABG, our data agree with the study of Kerbaul et al, 24 who reported a maximal release of NTproBNP 48 h after off-pump surgery, because the BNP values reached maximal values after 4 days, as suggested by our results (see Fig. 2).…”
Section: Discussionsupporting
confidence: 94%
“…[5][6][7][8]13 However, data in patients undergoing OPCAB is mostly limited to small studies. Similar to our results, previous studies in OPCAB patients also reported an early BNP rise, staring within 6 h of surgery, with peak levels occurring at 24-72 h. [14][15][16] The postoperative increase in BNP secretion is multifactorial and mediated primarily by direct myocardial ischemia and transient ventricular systolic or diastolic dysfunction that can by itself lead to BNP release even in the absence of evident myocardial necrosis. Increased myocardial wall tension, augmented regional wall stretch with transient atrial dilatation, also contributes to BNP release in these patients.…”
Section: Discussionsupporting
confidence: 90%
“…We analyzed the predictive value of the 3 biomarkers at various time points as markers of postoperative inotrope duration, ventilation and pleural drainage times, and ICU and hospital stays. Only the BNP level was a significant predictor of postoperative inotrope duration: odds ratio (OR) ¼ 4.9, 95% confidence interval (CI): 15, p ¼ 0.005. None of the variables including baseline and postoperative biomarker levels were found to significantly predict pleural drainage time, ICU or hospital stay.…”
Section: Resultsmentioning
confidence: 96%
“…Chello et al used BNP as a measure of successful functional recovery in patients undergoing coronary artery bypass graft surgery (CABG), and found that patients whose ejection fraction did not improve exhibited higher preoperative BNP levels [44]. In a sample of 60 patients undergoing CABG, Kerbaul et al found that elevated preoperative NT-proBNP concentration offered a good prediction of postoperative cardiovascular complications [45]. A preoperative cutoff concentration of 400 pg/ml had a sensitivity of 76% and specificity of 67% [accuracy = 74%] for predicting a subsequent cardiovascular event.…”
Section: Cardiac Surgerymentioning
confidence: 97%